Protecting transportation : implementing security policies and programs - Johnstone, R. William (Oxford : Elsevier Ltd., 2015)
Protecting Transportation: Implementing Security Policies and Programs provides a thorough overview of transportation security in the United States, with a focus on policy. The book coversall major transportation modes and puts the American security system into perspective against other national and international systems. Author R. William Johnstone, a transportation security expert and member of the 9/11 Commission staff, discusses how the current transportation security system came to be and how it is performing. Whether you are a current or aspiring transportation security professional, a policymaker, or an engaged citizen, Johnstone's presentation equips you to understand today's issues and debates on a problem that affects every member of the global community. Transportation security has evolved in the years since 9/11 from a relatively modest, sporadic undertaking into a multi-billion dollar enterprise employing tens of thousands. Protecting Transportation describes how that system is organized, funded, and implemented.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (EBSCO, viewed February 9, 2015).
Elsevier
Keywords: Transportation -- Security measures -- United States; POLITICAL SCIENCE / Political Freedom & Security / Law Enforcement; Transportation -- Security measures; United States; Electronic books